Semantic of Archaisation and its manifestations in contemporary Iraqi Plastic Art: Semantik Arkaisasi dan manifestasinya dalam seni rupa kontemporer Irak - Dr. Bashar Jawad Noumi (Academia Open, 2026)
General Background Contemporary Iraqi painting has evolved through continuous dialogue between inherited artistic traditions and modern aesthetic discourses shaped by social and cultural change. Specific Background Iraqi artists employ form, symbolism, and compositional structures to negotiate identity, modernity, and visual expression within a shifting historical context. Knowledge Gap Despite extensive discussions on Iraqi modern art, limited studies have systematically examined aesthetic form as a central interpretative axis connecting visual structure and cultural meaning. Aims This study aims to analyze aesthetic form in contemporary Iraqi painting and interpret its role in articulating modern artistic identity. Results The findings demonstrate that aesthetic form functions not merely as a visual arrangement but as a symbolic system reflecting social realities, cultural memory, and artistic adaptation. Novelty This research offers an integrated interpretative perspective that positions aesthetic form as a key mediator between tradition and modernity in Iraqi painting. Implications The study contributes theoretically to modern art discourse and provides a contextual framework for future analyses of contemporary Arab visual art. Keywords: Contemporary Iraqi Art, Aesthetic Form, Modern Painting, Visual Symbolism, Cultural Identity Key Findings Highlights: Aesthetic form represents cultural adaptation within contemporary Iraqi painting Visual structures embody dialogue between tradition and modern artistic expression Symbolic forms reflect social and historical realities in Iraqi modern art